Famous fails : mighty mistakes, mega mishaps & how a mess can lead to success! - Boyer, Crispin (National Geographic, 2016)
"This fun book of quirky failures and famous flops will keep kids laughing while they learn the importance of messing up in order to get it right. Science, architecture, technology, entertainment--there are epic fails and hilarious goof-ups from every important field. Silly side features help to analyze the failures: Lesson Learned, It Could Be Worse, Losing Combinations, and a Fail Scale help readers navigate the different kinds and scopes of the mistakes made. Read to learn what went wrong, what went right, and what kids can learn from each failed attempt"--